Регулювання інтересів зацікавлених сторін у емерджентному корпоративному управлінні - Хілуха (Ліпич), Оксана Анатоліївна; Khilukha, O. A. (Інститут трансформації суспільства, Інститут регіональних досліджень ім. М. І. Долішнього НАН України, 2015)
У статті сформовано поняття «емерджентне корпоративне управління» як управління, що являє собою інститут взаємодії між акціонерами та менеджментом корпорації, включаючи наглядову раду,правління, а також ревізійну комісію, іншими зацікавленими особами в умовах емерджентного ринку, за допомогою якого здійснюється керівництво компанією для досягнення цілей корпорації. Досліджено конфлікт інтересів стейкхол дерів, що пов’язаний iз відмінними цілями учасників корпоративного управління. Доведено, що для ефективного регу лювання розбіжностей цілей доцільно використовувати матрицю регулювання інтересів, котра дозволить збалансува ти інтереси учасників корпоративного управління шляхом врахування тих інтересів при розвитку корпорації, які є спільними для пріоритетних груп учасників корпоративного управління. Introduction. Recent research has documented differences among corporate governance in various organizations, which affects the company’s market value. A link between corporate governance and interest of stakeholders has been exa mined. Purpose. The purpose of the research is to determine the essential features of the corporate governance, to investigate and to regulate stakeholders’ aims. Methods. We have identified the notion of the emergent corporate governance with the use of the method of logical semantics. Further, we have analyzed the stakeholders’ interests by applying the method of systems analysis. The forms and methods of regulation of conflicts of interests in corporate governance were determined based on analysis, synthesis and classification methods. Results. In this paper, we have defined emergent corporate governance, as well as an interaction system between shareholders and management of the corporation. This system essentially involves balancing the interests of the board directors, audit commission and other stakeholders in the emergent environment. We have examined the stakeholders’ conflicts of interest which appear because of the difference in goals of the corporate management members. Conclusions. We have decided to use a coordination of interests’ matrix that will balance the interests of participants in corpo rate governance. The matrix considered the interests of stakeholders that are common for priority groups of stakeholders to enable the development of the organization.
Stakeholders' interests regulation in emergent corporate management
Keywords: корпоративне управління; заінтересовані сторони; мажоритарні акціонери; міноритарні акціонери; Corporate Governance; Emergent Corporate Governance; Stakeholders; Matrix of Interest Coordination